Teknik Menggambar Berbasis Finger Painting Pada SBdP Seni Rupa Siswa Kelas I SD Negeri 58 Kabupaten Lebong: Teknik Menggambar Berbasis Finger Painting Pada SBdP Seni Rupa Siswa Kelas I SD - Septeh Giovani Putri Septeh; Hasnawati; Bambang Parmadi (JURIDIKDAS, 2022)
This study aims to describe the techniques and results of drawing-based work finger painting in Cultural Arts and Fine Arts Skills for class I SDN 58 Lebong Regency. This type of research is a qualitative descriptive research. The research subjects were class teachers and first grade students at SD Negeri 58 Lebong Regency. Instruments on this study namely, the researchers themselves using observation guidelines, interviews, and documentation. Data analysis was carried out by collecting data, condensing data, presenting data, and drawing conclusions. Data collection techniques in the form of observation, interviews, and documentation studies. The results of this study are (1) based drawing techniques finger painting consist of blocking, 1 finger spiral and point, 1 finger straight, 1 finger rotate, 1 finger circular 1 finger raised curved, 2 oblique lines, 2 fingers rotate, 3 fingers wave, 3 fingers curved, and 3 fingers rotate from these techniques technique 3 rotary finger has not been applied in this study. (2) Results work of drawing technique based finger painting contains the elements and principles of fine art. the elements that exist are points, lines, planes, colors, and textures while those that are not yet available are shapes, space, and darkness. Then on the work of technique-based drawing finger painting has fulfilled the principles of fine art namely unity, rhythm, balance, center of attention, proportion, and contrast.